ANALISIS PERBANDINGAN MODEL ALTMAN Z-SCORE DAN MODEL ZMIJEWSKI DALAM MEMPREDIKSI KEBANGKRUTAN PERUSAHAAN - Misnah, Wati; Edyanus, Edyanus; Haryetti, Haryetti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
Bankruptcy is something that is highly avoided by every company, which usually begins with a problem of financial difficulties. Bankcruptcy prevention can be done by analyzing financial ration using a bankcruptcy prediction model. There are several models that can be used, namely Altman Z- Scoore and Zmijewski. This study aims potential to experience bankcruptcy and compare the accuracy of the Altman and Zmijewski models in predicting bankcruptcy in textile and footwear sub sector companies listed on the IDX for the 2017-2020 period. This type of research is quantitative descriptive research. Sampling using purposive sampling method. The result showed that there were 24 samples that were predicted to experience bankcrupty with the Altman model, and there were 22 samples that were predicted to experience bankcruptcy with the Zmijewski model. This study also show that the Altman model has an accuracy rate of 48,52 % while the Zmijewski is 72% so it can be concluded that the model with the highest level of accuracy is the Zmijewski model. Keywords : Bankrupty, Altman Z-Score, Zmijewski.